Ameloblastic fibrosarcoma developing 8 years after resection of ameloblastic fibro-dentinoma: A unique presentation. Issue 1 (January 2015) - Nagori, Shakil Ahmed; Jose, Anson; Bhutia, Ongkila; Roychoudhury, Ajoy; Kakkar, Aanchal
Abstract Ameloblastic fibrodentinoma (AFD) is a rare mixed odontogenic tumor, with biological behavior similar to ameloblastic fibroma (AF). These tumors are considered less invasive than solid ameloblastomas and have low tendency for recurrence. Sarcomatous transformation of AF is rare but well-recognized. Though of the same group, ameloblastic fibrosarcoma (AFS) developing after resection of AFD has not been reported in literature. We present a case of a well-encapsulated soft tissue AFS developing 8 years after aggressive treatment of previous recurrent AFD. The unusual biological behavior of AFD and the importance of long term follow-up of such patients are emphasized.